Differential modulation of hepatitis C virus replication and innate immune pathways by synthetic calcitriol-analogs. Issue 183 (October 2018) - Saleh, Maged; Welsch, Christoph; Cai, Chengcong; Döring, Claudia; Gouttenoire, Jérôme; Friedrich, Judith; Haselow, Katrin; Sarrazin, Christoph; Badenhoop, Klaus; Moradpour, Darius; Zeuzem, Stefan; Rueschenbaum, Sabrina; et al.
Graphical abstract: Highlights: Identification of calcitriol-analogs with intrinsic inhibitory effects against HCV replication. Distinctive interactions of calcipotriol as the lead analog with critical VDR regulatory residues. Differential impact of calcipotriol on innate immune pathways. Abstract: Background and Aims: Vitamin D signaling is involved in infectious and non-infectious liver diseases, yet the natural vitamin D metabolites are suboptimal therapeutic agents. In the present study, we therefore aimed to explore the potential and mechanism of selected calcitriol analogs to regulate the hepatocellular transcriptome and to inhibit hepatitis C virus (HCV) in comparison with calcitriol. Methods: Human hepatoma cell lines and primary human macrophages were stimulated with calcitriol and selected calcitriol analogs. The effect of calcitriol and its derivatives on hepatocellular gene expression and vitamin D receptor (VDR) signaling as well as on replication of HCV were assessed by quantitative PCR, microarray analyses and in silico analyses of ligand-VDR complexes. Results: The structurally related vitamin D analogs calcipotriol and tacalcitiol, but not calcitriol itself, suppressed HCV replication in a VDR-dependent manner. Using a residue-interaction network approach we outline structural and functional differences between VDR-ligand complexes. In particular we find characteristics in the VDR structure bound to calcipotriol with distinct local residue interaction patterns that affect key functional residues that pertain to the VDR charge clamp, H397 and F422, a VDR regulatory element for interaction with co-activators and -repressors. As a consequence, we show calcipotriol in comparison to calcitriol to induce stronger regulatory actions on the transcriptome of hepatocytes and macrophages including key antimicrobial peptides. Conclusion: Calcipotriol induces local structure rearrangements in VDR that could possibly translate into a superior clinical potential to execute important non-classical vitamin D effects such as inhibition of HCV replication.